The processes of incorporating human rights into the curriculum at Argentine universities (Papeles, 2026)
Introduction: This article explores how Human Rights are being incorporated into the curricula of Argentine public universities that are members of the Interuniversity Network for Human Rights. Methodology: Using a qualitative and exploratory approach, institutional programs and resolutions were analyzed, and interviews were conducted with ten leaders from five national public universities. Results and discussion: The research was structured around three dimensions: the leaders’ trajectories, the characteristics of the curricular spaces, and the dynamics of implementation. The findings show that the processes of curricularization are diverse and depend, to a large extent, on the academic activism of local actors, who promote these spaces based on their militant backgrounds or previous social commitments. In addition, there are different ways of including human rights content—such as elective or compulsory subjects—generally in social sciences, although there are attempts to extend mainstreaming to other academic units. The most recent institutional strategies, such as Plenary Agreement N.º 1169/22 of the National Interuniversity Council, are also highlighted. Conclusions: It is concluded that, although progress has been made, challenges remain related to institutional resistance, ideological prejudices, and the difficulty of mainstreaming Human Rights across non-traditional disciplines. Further research from the perspective of students is proposed.
Keywords: Human rights; education; university; curriculum